The Influence of Job Satisfaction and Organizational Culture on Employee Performance at the Regional Drinking Water Company (PDAM) in Luwu Regency - Satri Satri; Adil Adil; Ahmad Suardi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This study aims to determine the effect of job satisfaction and organizational culture on employee performance at the Regional Drinking Water Company (PDAM) in Luwu Regency. The population of this study were all employees of the Luwu District Drinking Water Company (PDAM) using quantitative methods. Sampling from the total population of 40 employees. Scoring data with a Likert Scale from SPSS calculation statistics. The results of this study state that job satisfaction has no effect on employee performance while organizational culture has a positive and significant effect on employee performance at the Luwu District Drinking Water Company (PDAM).